Condition monitoring of ship propulsion systems: State-of-the-art, development trend and role of digital twin - Nejad, Amir R.; Purcell, Etienne; Valavi, Mostafa; Hudak, Roman; Lehmann, Benjamin; Guzmán, Francisco Gutiérrez; Behrendt, Felix; Böhm, Angelo; von Bock und Polach, Rüdiger Ulrich Franz; Nickerson, Brendon M.; Bekker, Anriëtte; Drazyk, Withold (Volume 7: Polar and Arctic Sciences and Technology, 2021)
This paper describes the current implementations and development trends of condition monitoring as it pertains to ship propulsion systems. In terms of total incidents in the shipping industry in the last five years, failures relating to the propulsion system represent the majority. Condition monitoring offers effective early detection of failure which translates to increased reliability and decreased maintenance costs. Current industrial practices are often limited to performance monitoring rather than condition monitoring. Special focus is afforded to how condition monitoring is implemented on board ships, which regulatory codes are relevant and the summary of state-of-the-art research in marine machinery. Moreover, operation and monitoring in extreme environmental conditions, such as the Arctic and Antarctic with ice impact on the propulsion has been discussed. The new developments, in particular, digital twin approaches in health and condition monitoring have been highlighted, considering its pros and cons and potential challenges.